The The Relationship Between Workload, Work Stress, Work Environment, and Management Role on Firefighter Performance - Gita Asmarani; Bayu Yoni Setyo Nugroho (Health Science Udinus, 2026)
Employee performance is an important factor in determining the success of an organization in achieving its established goals. At the Semarang City Fire Department, employees are required to work quickly, accurately, and responsively in emergency situations, making optimal performance essential. However, high job demands, psychological pressure, work environment conditions, and organizational culture that have not been fully optimized may affect employee performance. In addition, firefighting is a high-risk occupation that may lead to increased workload and work stress. This study aimed to determine the relationship between workload, work stress, work environment, and organizational culture with employee performance at the Semarang City Fire Department. This study was conducted from October 2025 to April 2026 using a quantitative method with a cross-sectional approach. The sample consisted of 102 employees. The research instrument was a questionnaire that had been tested for validity and reliability. Data were analyzed using univariate and bivariate analyses with the Chi-Square test at a significance level of 5% (α = 0.05). The results showed that there was a significant relationship between workload and employee performance (p-value = 0.000), work stress and employee performance (p-value = 0.050), work environment and employee performance (p-value = 0.001), and organizational culture and employee performance (p-value = 0.000). It is recommended that the Semarang City Fire Department implement proportional workload management, enhance work stress prevention and management programs, improve work environment conditions, and strengthen organizational culture to optimize employee performance.